TEACHERS’ VOICES ON THE 2013 CURRICULUM FOR ENGLISH INSTRUCTIONAL ACTIVITIES - Maulidia Rachmawati Nur; Ahmad Madkur (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2014)
Curriculum is undoubtedly an inseparable part of education. In Indonesia, education curriculum has already undergone several changes. Among others, the newly introduced and implemented one is called Curriculum 2013 (K-13). Involving a “scientific approach”, this curriculum is expected to answer both the needs and the challenges to improve the quality of education in Indonesia. Nevertheless, the implementation of this curriculum gives birth to some pros and cons. The present paper is aimed at providing a picture of challenges, opportunities and teachers’ perception on the use of this curriculum in English teaching. The data were collected through in-depth interview to six English teachers in six pilot schools in Bogor and Lampung. The analysis shows that most teachers accepted the curriculum. However, according to them, the curriculum should be evaluated and further developed.